Do obedience pressure and incentive affect whistleblowing? - Putri, Fuadhillah Kirana; Wardani, Dewi Kusuma; Damara, Adam (Journal of Accounting and Investment, 2024)
Research aims: This study aims to empirically test the effect of obedience pressure on whistleblowing intentions and the role of incentives in moderating the obedience pressure on whistleblowing intentions.Design/Methodology/Approach: The method of analysis used in this research is experimental to test empirically the phenomenon of the causal relationship between obedience pressure and incentives on whistleblowing. This study uses a sample of experimental class results of Accounting Study Program students at Sarjanawiyata Tamansiswa University.Research findings: This study indicates that obedience pressure has a significant effect on whistleblowing intentions. On the other hand, incentives do not strengthen the positive effect of obedience pressure on whistleblowing intentions because, under high pressure, employees will still do whistleblowing in the presence or absence of incentives.Theoretical contribution/Originality: The results of this study are expected to be useful for future researchers who will examine whistleblowing, especially those influenced by obedience pressure and incentives. Practitioner/Policy implication: This research is expected to be an input for the organisation to consider that incentive reward is not the only way to enhance staff’s motivation to do whistleblowing.Research limitation/Implication: The limitations of this study were that it used student subjects as research participants, the research instrument had not explicitly described the amounts of incentives provided by the company to whistleblowers, and only examined the role of incentives in moderating obedience pressure on whistleblowing intentions.